Digital painting and rendering for theatrical design : using digital tools to create scenic, costume, and media renderings - Gillette, Jen (Routledge, 2024)
"Digital Painting and Rendering for Theatrical Design explores the tools and techniques for creating dazzling, atmospheric, and evocative digitally painted renderings for scenic, costume, and projection/integrated media design. By focusing on technique rather than the structure of a particular software, this book trains theatrical designers to think and paint digitally, regardless of the software or hardware they choose. The text begins with the construction of the artist's physical and digital workspace, then delves into an explanation of tool functionality, technique-building exercises, and examples from professional theatrical designers to help contextualize the concepts presented. Each chapter gradually progresses in complexity through skill-building exercises and advanced tool functionality, covering concepts like brush construction, various forms of masking, and layer interaction. The book explores various methods of constructing a digital rendering, including producing digital paintings that look like traditional media and photo bashing - the practice of using extant photographs to create a collaged image. Concepts are contextualized throughout the text using illustrations, quotes, and interviews with working professional designers. This beautifully illustrated guide is written for professional theatrical artists, students of theatrical design, and other visual artists looking to broaden their digital painting skillset"--